RESPOSTAS AUTOMÁTICAS PARA MELHORIA DA SEGURANÇA EM SISTEMAS DE DETECÇÃO DE INTRUSOS - SANTOS, Glenda de Lourdes Ferreira dos (2003)
The development of approaches for proving fast reactions against intruders and attackers have been one of the most important requirements in the critical defense of computer networks, since the intrusion occur quickly, demanding reactions without human intervention. These approaches should be able to, autonomously, respond to attacks and deal with several important aspects of the computer security problem in order to reduce the system administrator s workload Such approaches can offer larger reliability and effectiveness in the detection and response processes, a higher rate of security to private networks, better defense possibilities and, in addition, minimize the intruder's change of success. This research work deals with the specification of a society of intelligent agents for assessment and enhancement of intrusion response systems in computer networks. The proposal of the model of intrusion response system (IRS) be based on in several available architectures, in order to look for better solutions for the problems faced in the modelling of a system of that level. With that, was modeled a system to approach the main desirable functionalities for a system of active answers. The system, as part of the NIDIA (Network Intrusion Detection System based on Intelligent Agents) (Lima, 2001), is formed by a society of agents that are responsible for the functions of identification of the characteristic of the attack, choice of the best reaction strategy and for the execution of the response.The society is composed by agents able to determine and apply automatically corrective actions against attacks classified according to a given severity taxonomic model. In the proposed model was looked for to define response to intrusions for abuse and for anomaly to guarantee a lower robustness to the system.